Estimación de precios hedónicos para propiedades residencial y comercial en la ciudad de Bogotá - Melo Martínez, Carlos Eduardo; Melo Martínez, Oscar Orlando (Ingeniería, 2008)
The estimation of econometric models is quite basic in order to determinate the value of real estate taxes that the owners of properties must to pay. In this work is necessary to analyze structural and locational characteristics to deter minate the construction meter square value. Also, five hedonic regressions are developed; the first one to all the city and the others four models for residential and commercial economics activities. The regression models are estimated by using of ordinary least square and then are used to obtain implicit prices for construction of properties attributes.